Use of X-ray computed tomography for understanding localised, along-the-channel degradation of polymer electrolyte fuel cells. (20th August 2020) - Hack, Jennifer; Rasha, Lara; Cullen, Patrick L.; Bailey, Josh J.; Neville, Tobias P.; Shearing, Paul R.; Brandon, Nigel P.; Brett, Dan J.L.
Abstract: The need to understand the effects of degradation in polymer electrolyte fuel cells (PEFCs) has led to the development of in-situ and operando imaging studies of failure mechanisms occurring in their constituent materials, but studies using X-ray computed tomography (X-ray CT) for imaging have focussed primarily on a single region of the PEFC flow channel. Whilst studies have shown local variation in degradation rates using electrochemical techniques, this work employs identical-location X-ray CT imaging to elucidate the local degradation of a membrane electrode assembly (MEA) at various locations along-the-channel of a serpentine flow field. Using a carbon corrosion specific accelerated stress test (AST), in-depth analyses of the catalyst layers (CLs) and crack network allow for quantification of the material's degradation at the inlet, middle and outlet regions of the flow channel on the cathode side. Imaging of the regions was done after 0, 2000 and 5000 cycles and results show significant regional variation in the extent of degradation of the cathode CL. The order of degradation was found to be outlet > middle > inlet, with the outlet CL found to be thinner than the middle and inlet regions, with a greater extent of cracking. Furthermore, additional land and channel degradation effects were probed, with the land regions found to be less degraded than channel regions. This work further highlights the need to understand and develop ASTs that can promote a more uniform degradation rate across an MEA. Graphical abstract: Image 1 Highlights: Combined miniature fuel cell and X-ray computed tomography. Identical-location X-ray CT along-the-channel of a serpentine flow field during accelerated stress testing. Significant regional variation in the extent of degradation of the cathode. Fuel cell carbon corrosion ASTs do not age electrodes homogeneously.